Characterization of the complete chloroplast genome of Plumeria rubra cv. Acutifolia (Apocynaceae) - Wang, Dong-Lan (Mitochondrial DNA B Resour, 2020)
Plumeria rubra cv. Acutifolia is a widely planted landscape tree in the subtropics. In this study, the complete chloroplast genome of P. rubra cv. Acutifolia was determined through Illumina sequencing method. The complete chloroplast genome has a length of 153,912 bp, containing a small single-copy region (18,036 bp), a large single-copy region (84,852 bp), and a pair of IR regions (25,512 bp). The chloroplast genome possesses 130 genes, including 85 CDS, 37 tRNA genes and 8 rRNA genes. P. rubra cv. Acutifolia exhibited the closest relationship with P. cubensis in phylogenetic analysis.